Pembentukan Spiritualitas dan Karakter Jemaat Kristen di Arab Saudi melalui Pelayanan Lintas Budaya: Sebuah Model PKM Berbasis PAK - Lucky Antonio; Pujiwati Pujiwati; Mulianto Mulianto (Jurnal Kemitraan Masyarakat, 2025)
Cross-cultural ministry is a tangible manifestation of the Great Commission of Christ, which calls the church to reach all nations without geographical or cultural boundaries. This article describes the experience of spiritual ministry among the diaspora Christian community in the Middle East conducted by a team from the Kerusso Theological Seminary of Indonesia. The activity not only aimed to strengthen the faith of the congregation living under cultural and social pressures but also served as a means of nurturing contextual Christian spirituality and character. Through revival services, Bible teaching, and pastoral accompaniment, the congregation experienced a genuine transformation of faith—from weakness to steadfastness and hope. This study affirms that cross-cultural ministry is not merely a mission activity but a concrete expression of transformative and participatory Christian education. It demonstrates that when ministry is carried out with contextual understanding and empathy, profound spiritual change can occur even amid intercultural challenges.